A LC-MS3 strategy to determine lamotrigine by Q-Q-trap tandem mass spectrometry coupled with triple stage fragmentation to enhance sensitivity and selectivity. Issue 38 (10th September 2021) - Shi, Meiyun; Jiang, Qiuhong; Lyu, Qiushi; Yuan, Zhengting; Deng, Lili; Yin, Lei
Abstract : The novelty of this study is the MS 3 technique resulting in high selectivity and high sensitivity. Abstract : A high-performance liquid chromatography tandem mass spectrometry cubed (HPLC/MS 3 ) method was developed and validated to quantify lamotrigine in human plasma with carbamazepine as an internal standard. The HPLC/MS/MS system is composed of a Shimadzu UFLC XR high-performance liquid chromatograph coupled with a hybrid linear ion trap triple quadrupole mass spectrometer. Following simple protein precipitation with methanol, the separation of lamotrigine and carbamazepine was performed on an Agilent Poroshell 120 SB-C18 column (4.6 × 50 mm, 2.7 μm) using gradient elution with 0.1% formic acid in water (solvent I) and 0.1% formic acid in methanol (solvent II) at a flow rate of 0.8 mL min −1 . The total run time for each sample was 5 min. The method was validated for accuracy, precision, linearity, lower limit of quantification (LLOQ), selectivity, and other parameters. The LC/MS 3 method was linear in the concentration range of 0.50–50.0 μg mL −1 ( R 2 ≥ 0.995). The LLOQ was 0.5 μg mL −1, requiring only 30 μL of human plasma. Intra- and inter-day accuracies were <6.17% and precisions were <11.4% at all concentrations. The absolute recoveries (%) and matrix effect (%) for lamotrigine in human plasma were between 83.8 and 90.7. The developed and validated LC-MS 3 assay was successfully applied to monitor the lamotrigine levels in human plasma after the administration of lamotrigine.